The Analysis of the Online Newspapers in Health Epidemics: A Comparison Between the Public Sphere of Mexico and Spain - Idoiaga Mondragón, Nahia (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2015)
The 2009 swine flu was a pandemic influenza involving H1N1 virus. This paper studies how the mass media have treated this issue by analyzing the largest circulation newspapers in Mexico and Spain. 167 news of the two newspapers from April 2009 to August 2010 were analyzed. First, a positive correlation between the coverage of the outbreak and influenza-infected people was found. Second, a positive correlation between the coverage of the flu in Spain and the representation of health as a problem for the Spanish was also found. Third, an ALCESTE showed five main classes. Implications for research on social representations and media coverage as well as on strategies resulting from media discourse to cope with threatening health crisis are discussed.